ANGLIKER, ERICA; TULLY, JOHN. CYCLADIC ARCHAEOLOGY AND RESEARCH. NEW APPROACHES AND DISCOVERIES. OXFORD: ARCHAEOPRESS, 2018. 362 p. ISBN: 978-1-78491-809-5. (Heródoto: Revista do Grupo de Estudos e Pesquisas sobre a Antiguidade Clássica e suas Conexões Afro-asiáticas, 2020)
Resenha - Cycladic Archaeology and Research